Molecular driver alterations and their clinical relevance in cancer of unknown primary site - Löffler, Harald; Pfarr, Nicole; Kriegsmann, Mark; Endris, Volker; Stenzinger, Albrecht; Weichert, Wilko; Krämer, Alwin (OncoTarget, 2016)
Oncotarget | https://doi.org/10.18632/oncotarget.10035 Harald Löffler, Nicole Pfarr, Mark Kriegsmann, Volker Endris, Thomas Hielscher, Philipp Lohneis, Gunnar Folprecht, Albrecht Stenzinger, Manfred Dietel, Wilko...